Investigation of the anti-inflammatory effects of caffeic acid phenethyl ester in a model of λ-Carrageenan–induced paw edema in rats - Semis, Halil Sezgin; Gur, Cihan; Ileriturk, Mustafa; Kaynar, Ozgur; Kandemir, Fatih Mehmet (SAGE Publications, 2021)
In the present study, it is aimed to evaluate the effects of caffeic acid phenethyl ester (CAPE) against acute paw inflammation induced by carragenan (Carr) at macro and micro levels. Therefore, in this study, 1 hour after administering intraperitoneal of indomethacin (Ind) or CAPE (10 and 30 mg/kg body weight) to Sprague Dawley rats, Carr was injected intraplantarly into their right paws. The paw volumes of the rats were measured with a plethysmometer until the 4th hour. Also, X-ray and thermal camera images were taken to determine edema and temperature changes. At the end of the study, after the paw tissues and serums were taken, oxidative stress and inflammation status were determined using biochemical, molecular, and western blot techniques. In addition, lipid and protein profiles in paw tissue were determined using HPTLC and electrophoresis methods. The results depicted that a high dose of CAPE against Carr-induced inflammation may be almost as effective as Ind used as reference.
Keywords: Male; Anti-Inflammatory Agents; Phenylethyl Alcohol; Carrageenan; Rats; Rats, Sprague-Dawley; Disease Models, Animal; Oxidative Stress; Caffeic Acids; Animals; Edema